Von Hippel-Lindau disease: report of an adolescent case emphasizing the diagnostic aspects - Tınaztepe, Keriman; Bilgiç, Sevgül; Önol, Behsan; Erbengi, Aykut; Yuluğ, Aydın (The Turkish Journal of Pediatrics, 1987)
An adolescent case of von Hippel-Lindau disease is reported. The patient presented with symptoms of an intracranial mass and a cerebellar hemangioblastoma was excised. With the tentative diagnosis of von Hippel-Lindau disease, a more detailed fundus examination including fluorescein angiography was carried out and asymptomatic retinal angioma was detected. The angioma was then treated by photocoagulation. Even though the disease usually manifests itself in early adulthood, it may occasionally be seen in adolescence. Therefore, pediatricians should recognize the various manifestations of the disease and search for the other possible components when one of them is detected.